2016
DOI: 10.1172/jci.insight.87460
|View full text |Cite
|
Sign up to set email alerts
|

Gene pathway development in human epicardial adipose tissue during early life

Abstract: Studies in rodents and newborn humans demonstrate the influence of brown adipose tissue (BAT) in temperature control and energy balance and a critical role in the regulation of body weight. Here, we obtained samples of epicardial adipose tissue (EAT) from neonates, infants, and children in order to evaluate changes in their transcriptional landscape by applying a systems biology approach. Surprisingly, these analyses revealed that the transition to infancy is a critical stage for changes in the morphology of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Interestingly, Sacks et al, reported that UCP-1 expression was fivefold higher in EAT than substernal fat, and undetectable in subcutaneous fat, suggesting that EAT could have «brown» fat properties to defend myocardium and coronary arteries against hypothermia (40). The authors further demonstrated that the structure and architecture of EAT differs among the neonate, infant, and child with more genes implicated in the control of thermogenesis in EAT of neonates, and a shift towards lipogenesis through infancy (230).…”
Section: Thermogenesismentioning
confidence: 98%
“…Interestingly, Sacks et al, reported that UCP-1 expression was fivefold higher in EAT than substernal fat, and undetectable in subcutaneous fat, suggesting that EAT could have «brown» fat properties to defend myocardium and coronary arteries against hypothermia (40). The authors further demonstrated that the structure and architecture of EAT differs among the neonate, infant, and child with more genes implicated in the control of thermogenesis in EAT of neonates, and a shift towards lipogenesis through infancy (230).…”
Section: Thermogenesismentioning
confidence: 98%
“…One approach currently being adopted is the use of large-scale bioinformatics to describe and identify novel pathways. To date, this has only been undertaken on epicardial adipose tissue taken from neonates and infants who have undergone heart surgery [25] . These analyses have further revealed that the transition to infancy is a critical stage for changes in adipose tissue morphology that is reflected by a unique pattern of gene expression that included a significant proportion of thermogenic gene transcripts ( ∼ 10%).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Access to EAT and PAT is severely limited due to their physiological location and the invasive nature of the sampling procedure. Therefore PAT samples were taken from 66 patients (age: 66±8 years) with coronary artery disease (CAD) [24] and the EAT samples were taken from 11 neonates (6 to 24 days old), 28 infants (40 days to 1 year-old) and 7 children (2 to 7 years old) with congenital heart disease (CHD) [25].…”
Section: Resultsmentioning
confidence: 99%